Theodor Fontane als Kunstkritiker - Aus der Au, Carmen (Schriften der Theodor Fontane Gesellschaft, 2017)
This monograph is the first comprehensive appraisal of Theodor Fontane`s complete works of art criticism in all its relevant contexts. It situates Fontane`s writings on art between the realms of the Berlin School`s fully differentiated academic art scholarship and that of feuilleton art criticism, and includes references to his personal writings and fictional works.